Passive target tracking using transmitters of opportunity - Shephard, D; Richards, G.A (IET Seminar on Target Tracking and Data Fusion: Algorithms and Applications, 2008)
Scattering of signals from commercial television or radio channels from air and surface targets can be detected by one or more passive receivers. The received signals can be processed to give bistatic range and range rate measurements on targets. This paper considers tracking algorithms to convert the measurements to target tracks using data from a demonstration receiver, with emphasis on the problem of track initiation for low SNR targets where there are many false detections. It is shown that it is possible to track targets in this type of environment. Further development and tuning is required to minimise the number of false tracks initiated.